Teacher Professional Development in the Secondary Schools in Nepal: Some Opportunities and Challenges - Poudel, AmbikaPrasad (Rupantaran: A Multidisciplinary Journal, 2022)
Quality education has been one of the important concerns among the stakeholders in the field of education. Teacher professional development (TPD) is considered as one of the essential components for improving and reforming quality of education in the recent years. This article attempts at describing the existing TPD status of the secondary level schools in Nepal, and exploring the opportunities and challenges of TPD programme for the teachers in those schools. In the study, the Headmaster, and secondary level senior teachers were the informants; and an observation check list, and an interview questionnaire were used as the research tools to collect the information. The data were analyzed both descriptively and thematically. The study found that the secondary schools were quite poor regarding their performance of TPD activities. Some of the major advantages of the TPD programme to the teachers were that they got opportunities to take part in training and workshops; and to be involved in discussion and collaboration among the teachers. On the other hand, difficulties in the implementation of their knowledge and skills into the classroom, and lack of financial support for TPD activities were some of the major challenges of TPD process.